ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN PADA SITUS JUAL-BELI ONLINE - Setiawan, I Gede Andri; Sukardi, Sukardi (Jurnal Fokus Manajemen Bisnis, 2020)
The purpose of this study were to analyze (1) the influence of trust of the purchase interest of online shop consumers, (2) the influence of risk perception of theÂ purchaseÂ interestÂ ofÂ onlineÂ shopÂ consumers,Â (3)Â theÂ influenceÂ ofÂ use fulness perception of the purchase interest of online shop consumers, (4) the influence of price perception of the purchase interest of online shop consumers. The populations in this research areÂ student of Ahmad Dahlah University YogyakartaÂ CampusÂ One.Â TheÂ methodÂ sampleÂ is Â purposifÂ samplingÂ withÂ the numberÂ ofÂ sampleÂ asÂ muchÂ asÂ 100Â respondentsÂ fromÂ threeÂ FacultyÂ thatÂ is, EconomyÂ Faculty,Â PsycologyÂ Faculty,Â andÂ FTDI.Â CollectingÂ dataÂ using questionnairesÂ thatÂ wasÂ doneÂ validityÂ testÂ andÂ realibityÂ test.Â ThisÂ researchÂ was done by using multiple linear regression data analysis. TheÂ resultsÂ ofÂ thisÂ studyÂ indicateÂ thatÂ (1)Â theÂ trustÂ isÂ notÂ significant influence on consumer purchase interest of the sites online shop, this is evidenced by the significant valueÂ is biggerÂ than the probability alpha value of 0.05 (0,206 > 0.05), and the regression coefficient has aÂ positive value of 0.062; (2)Â theÂ trust is not significant influence on consumer purchase interest of the sites online shop, thisÂ isÂ evidencedÂ byÂ theÂ significantÂ valueÂ isÂ bigger Â thanÂ theÂ probabilityÂ alpha value of 0.05 (0, 0,234 > 0.05), and the regression coefficient has a positive value ofÂ 0.057;Â (3)Â theÂ usefulnessÂ perceptionÂ isÂ significantÂ influenceÂ onÂ consumer purchase interest of the sites online shop, this is evidenced by the significant value isÂ smallerÂ thanÂ theÂ probabilityÂ alphaÂ valueÂ ofÂ 0.05Â (0.000Â <Â 0.05),Â andÂ the regression coefficients has a positive value of 0.456; (4) the price perception is not significantÂ influence on consumer purchase interest of the sites online shop, thisÂ isÂ evidencedÂ byÂ theÂ significantÂ valueÂ isÂ bigger Â thanÂ theÂ probabilityÂ alpha value of 0.05 (0.066 > 0.05), and the regression coefficient has aÂ positive value ofÂ 0.111;Â andÂ (5)Â trust,Â riskÂ perception,Â usefulnessÂ perceptionÂ andÂ price perceptionÂ togetherÂ haveÂ anÂ effectÂ onÂ consumerÂ purchaseÂ interestÂ ofÂ theÂ sites onlineÂ shop,Â thisÂ isÂ evidencedÂ byÂ theÂ significant Â valueÂ isÂ smallerÂ thanÂ the probability alpha value of 0.05 (0.000 < 0.05). The R2 test results in this study was obtainedÂ R2 valueÂ ofÂ 0.413.Â ThisÂ showsÂ thatÂ purchaseÂ interestÂ isÂ influencedÂ by trust, risk perception, use perception, and priceÂ perception by 41.3%, while the remaining 58.7% is influenced by other factors not observed by the researcher or considered fixed.